Correlation between MUET and academic performance of electrical engineering students / Norlida Buniyamin, Rosni Abu Kassim and Usamah Mat - Buniyamin, Norlida; Abu Kassim, Rosni; Mat, Usamah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
This paper presents the findings of a case study to identify the impact of English Language Proficiency (ELP) on the academic performance of engineering students in a public university in Malaysia. The case study had the objective to find the correlation between students’ English language proficiency and their academic achievement. In this case study, the Malaysian University English Test (MUET) overall score was used as an indicator of English language ability and the students Cumulative Grade Point Average (CGPA) as an indicator of academic performance. The second objective of this study is to investigate and observe the effect of raising the MUET Band from Band 2 to Band 3 for admissions to studies in the field of Science, Technology, Engineering, and Mathematics (STEM) in undergraduate courses in public universities in Malaysia. In addition, the academic performance by gender was also analysed. Eighty-four students were sampled from an engineering program of a local public university. The results from this case study showed that English Language Proficiency to a certain extent does influence academic performance and that raising the MUET Band to Band 3 for admission will result in many potential students losing a place in a public university.